Introducing Therapeutic Robotics for Autism - Nawaz, Raheel; Ali, Sara (Emerald points., 2023)
Written accessibly from the user's perspective, Introducing Therapeutic Robotics for Autism is a must read for researchers from related disciplinary backgrounds including robotics, educational psychology, cognitive sciences, and ASD.